A diagram for capturing and predicting failure locations in notch geometries produced by additive manufacturing. (May 2020) - Solberg, Klas; Berto, Filippo
Graphical abstract: Highlights: In AM metals, fatigue does not initiate from the designed notch roots, but from surface defects adjacent. An analytical formulation for the diagram is proposed. The model is demonstrated on AM as-built Inconel 718 specimens. Abstract: In a recent work by the authors Solberg and Berto (2019), as-built notch geometries of Inconel 718 produced by selective laser melting was investigated under fatigue loading. One of the findings was that fatigue did not initiate from the notch roots, but from defects adjacent. A diagram was developed for capturing the failure locations. Here, a generalized formulation of the diagram is proposed. The model can be useful for developing understanding of which is the dominant feature determining the failure locations; local or global notch geometries. The diagram can be applied in various loading cases, ranging from fatigue to static loading.